Market shaping via digital public infrastructure for assistive technology in low- and middle-income countries - Will Wade; Sijung Hu; James Fleming (Frontiers in Rehabilitation Sciences, 2026)
Digital assistive technology (AT) is now delivered through a variety of platforms, including smartphones, cloud services, dedicated devices, and embedded systems rather than a single dominant form factor. However, in low- and middle-income countries (LMICs), affordability, connectivity, electrical reliability, service capacity, and uneven language infrastructure continue to determine which digital pathways can be deployed and maintained at scale. This perspective argues that market-shaping strategies should prioritise the development of shared digital infrastructure beneath the application layer; this includes representative datasets and language resources, reusable models and reference toolchains, and deployment pathways tailored to resource-constrained environments. It proposes a three-part Market Stack comprising governed data and language resources, reusable core models and reference pipelines, and localised commercialisation and service delivery by small and medium enterprises. The central argument is not to replace smartphones but to ensure that digital AT markets in constrained settings work best when innovators and procurers can choose among smartphone, dedicated, embedded, and hybrid solutions. Therefore, funders and policymakers should view data, language resources, and foundational tooling as public-interest investments that widen the range of assistive products available in LMIC markets.